A 249‐yr chronosequence of forest plots from eight successive fires in the Eastern Canada boreal mixedwoods. Issue 5 (18th March 2021) - Maleki, Kobra; Marchand, Philippe; Charron, Danielle; Lafleur, Benoit; Bergeron, Yves
Abstract: A combination of wildfires and defoliating insect outbreaks play an important role in the natural successional dynamics of North American boreal mixedwood forests, which, in the long term, change the post‐disturbance composition and structure of forest stands. After stand‐replacing disturbances (mainly wildfires), early successional hardwoods typically dominate the affected areas. Provided enough time following disturbances, the increasing recruitment of mid‐ to late‐successional softwoods as well as the mortality of hardwoods gradually change forest composition from hardwoods to admixtures of hardwood‐conifer species and conifer‐dominated stands in mid and late successional stages, respectively. Such mixedwoods are abundant across the southern Canadian boreal forest. In boreal Canada, mixedwoods are the most structurally heterogeneous forest ecosystems, are highly productive, and form an important source of timber supply. Here we present the EASTERN BOREAL MIXEDWOODS CANADA data set, which documents the changes in composition and structure of stands originating from eight different wildfires representing a chronosequence of 249 yr since fire in eastern Canada. This data set has been used in several different projects to study and model the influence of natural (e.g., insect outbreaks) and anthropogenic disturbances (e.g., harvesting) on the dynamics of post‐fire stands. The data set covers a high range of variability in stand composition and structure, explained by species establishment, dominance, and mixture. It thus constitutes a useful source of information to trace the dynamics of the main boreal tree species of eastern North America, from their establishment to their replacement at different spatial scales (e.g., from stand to landscape level). Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data. We are open to collaborate in developing or co‐authoring relevant research projects based on this data set.